Formulas for the computation of the Tutte polynomial of graphs with parallel classes - Eunice Mphako-Banda; Julian A. Allagan (Electronic Journal of Graph Theory and Applications (EJGTA), 2018)
We give some reduction formulas for  computing the Tutte polynomial of any graph with parallel classes. Several examples are given to illustrate our results.